Analysis of ground reaction force and electromyographic activity of the gastrocnemius muscle during double support - Andreia S. P. Sousa (2012)
Purpose: Mechanisms associated with energy expenditure during gait have been extensively researched and studied. According to the double-inverted pendulum model energy expenditure is higher during double support, as lower limbs need to work to redirect the centre of mass velocity. This study looks into how the ground reaction force (GRF) of one limb affects the muscle activity required by the medial gastrocnemius (MG) of the contralateral limb during step-to-step transition. Methods: Thirty-five subjects were monitored as to the MG electromyographic activity (EMGa) of one limb and the GRF of the contralateral limb during double support. Results: After determination of the Pearson correlation coefficient (r), a moderate correlation was observed between the MG EMGa of the dominant leg and the vertical (Fz) and anteroposterior (Fy) components of GRF of the non-dominant leg (r=0.797, p<0.0001; r=-0.807, p<0.0001) and a weak and moderate correlation was observed between the MG EMGa of the non-dominant leg and the Fz and Fy of the dominant leg, respectively (r=0.442, p=0.018; r=-0.684 p<0.0001). Conclusions: The results obtained suggest that during double support, GRF is associated with the EMGa of the contralateral MG and that there is an increased dependence between the GRF of the non-dominant leg and the EMGa of the dominant MG.